Ultra-efficient frequency comb generation in AlGaAs-on-insulator microresonators - Lin Chang (Nature Portfolio, 2020)
Despite larger nonlinear coefficients, waveguide losses have prevented using semiconductors instead of dielectric materials for on-chip frequency-comb sources. By significantly reducing waveguide loss, ultra-low-threshold Kerr comb generation is demonstrated in a high-Q AlGaAs-on-insulator microresonator system.